Political Direction of Environmental Management Law in Indonesia - Saputra, Muhammad Azhary Bayu; Mahardika, Ega Rijal; Kariim, Siti Almiraa (Universitas Negeri Semarang, 2023)
This paper examines the political trajectory shaping environmental management law in Indonesia. With its rich biodiversity and rapid industrialization, Indonesia faces complex challenges in balancing economic development with environmental conservation. The analysis begins with an overview of the historical context, tracing the evolution of environmental legislation from the colonial era to the present day. It explores how political dynamics, including shifts in governance structures, power relations, and socio-economic priorities, have influenced the development and enforcement of environmental regulations. The paper highlights key legislative milestones, such as the enactment of the Environmental Management Act in 1997 and subsequent revisions, as well as the establishment of agencies like the Ministry of Environment and Forestry. It also discusses the role of international treaties and agreements in shaping Indonesia's environmental legal framework. Furthermore, the paper evaluates the effectiveness of environmental laws in practice, considering challenges related to enforcement, capacity-building, and coordination among various stakeholders. It examines the role of civil society, the media, and grassroots movements in advocating for stronger environmental protection measures. Drawing on current trends and future projections, the paper concludes with an analysis of potential directions for Indonesian environmental management law. It considers the implications of political, social, and environmental factors, including the need for greater transparency, public participation, and adaptive governance mechanisms in addressing emerging environmental issues such as climate change, deforestation, and marine pollution.